The reversion of the burden of proof underlying the extended confiscation: between the Penal Code and the Drugs Act - Luiz Eduardo Dias Cardoso (Revista Brasileira de Direito Processual Penal)
The present article aims to analyze the extended confiscation, recently incorporated to the Penal Code (article 91-A) and to the Drugs Act (article 63-F), and focuses on a specific procedural issue, regarding the burden of proof underlying the extended confiscation. The research problem can be summarized as the following: does the extended confiscation work based on a reversion of the burden of proof? The hypothesis points that there are two answers: reversion of proof exists in the Penal Code, however, it cannot be found in the Drugs Act. This paper, which is justified by the theme's relevance and novelty, is guided by the deductive method, because it begins with broad considerations regarding the extended confiscation and aims to find a specific conclusion about the reversion of the burden of proof. Firstly, it presents the extended confiscation, emphasizing its legislative background, its main characteristics and Brazil’s laws. Later, the article shows how the proof regarding the extended confiscation is produced according both to the Penal Code and to the Drugs Act; finally, it reflects on the consequences following the reversion of the burden of proof. The research's result confirms the hypothesis initially drawn.